Migrant parents at high school: Exploring new opportunities for involvement - Melnikova, Julia (Frontiers in Education, 2022)
This article examines the at-school opportunities Norwegian high schools provide for involving migrant parents in their children’s education. The legal and societal expectations of systematic school-home cooperation with all parents at this time of transition to higher education or employment are relatively new in Norway. Thus, how schools act on these expectations as they meet migrant parents is under-researched. To address this gap, interviews with four leaders of three high schools with different sociocultural profiles and observations of meetings with parents at one of the schools were conducted as a part of this study. Examined through a Bourdieusian lens, parental involvement—or rather traditional lack of at-school parental involvement outside crises—can be interpreted as a form of high-school doxa. This unquestionable truth is now challenged as more rights are granted to parents, and new heterodox beliefs and discourses about parents of adolescents at school emerge. At the same time, the schools in the focus of this study appear to have limited room for imagining forms and content of non-crisis communication with the home, especially when parents do not directly claim their rights, as is true for many migrant families. This study thus contributes to the existing research on parental involvement and home-school relations by emphasizing the need for a professional discussion on more equitable and better situated forms of engaging parents, as well as the school’s areas of responsibility in including families in educational communities.